Qualitative Study of Two and Four-Wheel Tractor Use in Timor-Leste’s Five Districts - Arcanjo De Jesus; Iqbal Iqbal; Abdul Azis (Program Studi Teknik Pertanian Universitas Hasanuddin, 2025)
Agricultural mechanization is increasingly promoted to address labor constraints and improve the timeliness of field operations in rice-based farming systems. This study qualitatively examines the use of two-wheel and four-wheel tractors in five districts of Timor-Leste (Manufahi, Covalima, Bobonaro, Manatuto, and Ainaro) and identifies key barriers and strategic implications for strengthening mechanization. Field data were collected through observation, questionnaires, and farmer interviews, and were synthesized using a SWOT (Strengths–Weaknesses–Opportunities–Threats) approach. Results indicate that tractor utilization remains limited across all districts, with most farmers reporting no tractor use (72.5–85.0%). A system-level assessment of four-wheel tractor (TR4) adequacy shows a substantial demand–availability gap: 124 units are available against an estimated requirement of 293 units (≈42.3% fulfillment), implying a shortfall of 169 units and potential bottlenecks during peak land preparation periods. District-level efficiency indications vary, suggesting different levels of operational pressure and the need for targeted interventions. The SWOT synthesis highlights productivity and efficiency gains as key strengths, while financial limitations, uneven distribution, and limited maintenance/spare-part access remain major weaknesses. Recommendations include strengthening operator and farmer training, improving maintenance and spare-part services (service centers and mobile repair), and enhancing access mechanisms such as managed hire services and context-appropriate financing to support reliable and timely tractor utilization